Differences in Skills of Passing Down With Two on Two Playing Model in Volleyball Games on Students of Sdk Sang Timur Malang City - Halawa, Saverius; Kusmawati, Wiwik; Kurniawan, Rubbi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The results of this study aim to determine the differences in underhand passing skills with the two-on-two playing model in volleyball games for students at SDK Sang Timur, Malang City. The research method is a quasi-experimental method. The sampling technique is simple random sampling. The sample is 20 students in class 5 A as the experimental class and 20 students in class 5 B as the control class. The data collection technique uses tests and non-tests. The instruments are multiple-choice objective tests and non-test instruments in the form of questionnaires. The data obtained were analyzed using the prerequisite test of normality and homogeneity tests. The results of the t-test that have been carried out with the SPSS program, obtained that the t-count value is greater than the t-table value, meaning that there is a significant difference in underhand passing skills with the two-on-two playing model in volleyball games for students at SDK Sang Timur, Malang City.